2012
DOI: 10.1371/journal.pone.0042242
|View full text |Cite
|
Sign up to set email alerts
|

Rare Primary Mitochondrial DNA Mutations and Probable Synergistic Variants in Leber’s Hereditary Optic Neuropathy

Abstract: BackgroundLeber’s hereditary optic neuropathy (LHON) is a maternally inherited blinding disorder, which in over 90% of cases is due to one of three primary mitochondrial DNA (mtDNA) point mutations (m.11778G>A, m.3460G>A and m.14484T>C, respectively in MT-ND4, MT-ND1 and MT-ND6 genes). However, the spectrum of mtDNA mutations causing the remaining 10% of cases is only partially and often poorly defined.Methodology/Principal FindingsIn order to improve such a list of pathological variants, we completely sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 59 publications
3
61
1
1
Order By: Relevance
“…However, a stringent pathogenicity of such variants is often hard to establish. 3 In a considerable fraction of clinically clear-cut patients, no causative mtDNA mutation have been found; and with an additional pronounced sex-biased penetrance, the genetic etiology of LHON remains complex. 4 It has been suggested that the specific haplogroup background of genetically verified LHON patients has an influence on disease manifestation, 5 and several so-called secondary LHON-associated mtDNA variants have been claimed to play a role in penetrance and disease expression, though the significance of such variants still remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, a stringent pathogenicity of such variants is often hard to establish. 3 In a considerable fraction of clinically clear-cut patients, no causative mtDNA mutation have been found; and with an additional pronounced sex-biased penetrance, the genetic etiology of LHON remains complex. 4 It has been suggested that the specific haplogroup background of genetically verified LHON patients has an influence on disease manifestation, 5 and several so-called secondary LHON-associated mtDNA variants have been claimed to play a role in penetrance and disease expression, though the significance of such variants still remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…1,10,[38][39][40][41] In addition, the m.3733G>A mutation was a rare mutation, as in the case of European origin. 17,18 In this cohort, the m.3635G>A mutation in the Chinese population appeared to be more common than European patients. 16,42 Furthermore, the m.3866T>C mutation was presented more in Asian than in European patients with LHON.…”
mentioning
confidence: 63%
“…[15][16][17] Thus, the MT-ND1 gene is proposed to be another hot spot for mutations associated with LHON. 18 However, the mutational spectrum and incidence in the MT- To further understand the pathophysiology of LHON, we performed the clinical and genetic analysis of 1281 Han Chinese probands (patient or member of the family that brings a family under study) with LHON.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cause a variable clinical manifestation, from vision loss to complex neurological disorders called LHON+ 2. There are also 18 candidate primary LHON mutations found only in a single family or in a single case (MITOMAP, http://www.mitomap.org).…”
mentioning
confidence: 99%